Changes in the Political Behavior of Towani Tolotang as a Minority Religious Group: Fiqh Al-‘Aqaliyyāt Perspective - Jubba, Hasse; Ahmad Sunawari Long; Zuly Qodir; Umar Werfete; Muhamad Nastain (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
This article is aimed at explaining how the political behavior of Towani Tolotang, a minority religious group in Indonesia, unfolds by using fiqh al-‘aqaliyyāt (Islamic jurisprudence of the minority) perspective. Accordingly, the current article discusses three aspects. First, the Towani Tolotang’s political activities. This correlates with the group’s position, which in terms of quantity is far fewer than the Muslim majority. Second, the national constitution’s provision ensures the rights of each citizen to participate in various aspects of life, including political freedom regardless of their position and status. Third, the Muslim majority group’s acceptance of the Towani Tolotang’s political activities. The data analyzed in the research were collected by observing the daily life of the Towani Tolotang, interviewing some informants, and studying document as well as literature studies on relevant documents and literary sources. According to the data analyses, it was found that there are apparent changes in the political behavior of this particular minority group, which not only include the distribution of support given to various political parties but also the active engagement of the group’s elites and followers in the general election wherein some of them have even become a member of the local level legislative body. The present article asserts that the Towani Tolotang is one of the minority groups in Indonesia that has acquired space to actively participate in politics, although occurring at the local level. This is not only due to the Muslim majority’s acceptance, but the Towani Tolotang group’s fraternization with Muslims as well.